Home advantage and technical-tactical performance indicators in male soccer college teams (NCAA Division I 2010-2020) - Popp, L.; Caicedo-Parada, S.; Palao, J. M. (Perceptual and Motor Skills, 2025)
Purpose The purpose of this study was to analyze the evolution of home advantage (HA) effect in NCAA D1 men`s soccer (2010-2020) in relation to the level of a team.